PP11 Association between atopic disorders and childhood type 1 diabetes: A population-based case control study in the Middle East. (2nd September 2014) - Memon, A; Polack, S; Al-Khawari, M; Qabazard, M; Al-Adsani, A; Abdul-Rasoul, M; Gulati, R; Shaltout, A; Suresh, A
Abstract : Background: Worldwide, there has been a steady increase in the incidence of childhood type 1 diabetes over the last three decades, and the incidence is estimated to double between 2005 and 2020 in most countries. Substantial increases in incidence have also been observed in countries in the Middle East, and Kuwait now has the 4th highest incidence of type 1 diabetes in the world (22.3/100, 000/year). We conducted a population-based case-control study in Kuwait (which is the first study on the subject in the Middle East) to identify neonatal and early childhood factors that may influence the risk of type 1 diabetes. Methods: The study included 376 children with type 1 diabetes (aged 0–19 years at diagnosis and registered at the Kuwait Childhood Diabetes Registry) and a similar number of individually matched (on age, gender, nationality, and district of residence) population control subjects. Mothers of children were interviewed to obtain information on infant feeding (including breastfeeding), physician diagnosed diseases and candidate neonatal and early childhood risk factors before the date of diagnosis/pseudodiagnosis of type 1 diabetes in cases/controls. Results: The prevalence of atopic eczema and asthma was significantly lower in cases compared with controls (6% vs. 18% and 9% vs. 24%, respectively). In the multivariate conditional logistic regression analysis, atopic eczema (OR=0.3, 95% CI: 0.1–0.5) and asthma (OR=0.3, 95% CI: 0.2–0.5) were inversely associated with the risk of type 1 diabetes, after adjustment for maternal age at birth, infant feeding, other diseases and stressful life events. There was also an inverse association with history of tonsillitis during the first year of life (OR=0.5, 95% CI: 0.3–0.7). Conclusion: Our findings suggest that there is a significant reduction in the prevalence of atopic eczema and asthma in children with type 1 diabetes, and that atopic disorders may confer partial protection against type 1 diabetes. This association between Th2-biassed immune response/atopic disorders and Th1-biassed autoimmune diseases such as type 1 diabetes needs further investigation.